2020
DOI: 10.1016/j.orcp.2020.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Self-quarantine and weight gain related risk factors during the COVID-19 pandemic

Abstract: Objective: The purpose of this study was to quantify the impact that self-quarantine has on behaviors associated with weight gain. Methods: This was a quantitative descriptive/correlational research design. Research announcement was sent out via Facebook to 1200 possible participants. Six surveys were condensed into a single Survey Monkey questionnaire for participants to complete. Surveys asked questions relating to risk factors linked to weight gain. Results: Ninety-one percent of our sample stated they spen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
448
8
57

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 461 publications
(602 citation statements)
references
References 30 publications
51
448
8
57
Order By: Relevance
“…Excessive energy intake may result in increased fat storage capacity and weight gain, even obesity, insulin resistance and lipotoxicity in severe cases (14). The problematic eating behaviors such as frequent overeating, snacking after dinner, eating in response to stress are the risk factors for weight gain during the self-isolation in USA and Poland (15,16). Even though the weight gain was slight relatively, this small change in weight for adults may contribute to substantial increases over decades (5).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive energy intake may result in increased fat storage capacity and weight gain, even obesity, insulin resistance and lipotoxicity in severe cases (14). The problematic eating behaviors such as frequent overeating, snacking after dinner, eating in response to stress are the risk factors for weight gain during the self-isolation in USA and Poland (15,16). Even though the weight gain was slight relatively, this small change in weight for adults may contribute to substantial increases over decades (5).…”
Section: Discussionmentioning
confidence: 99%
“…The rst outbreak of COVID-19 in Wuhan, China, which has experience in ghting against SARS, thus Chinese government has taken many effective measures in the early stage, such as "lockdown " the city, the order to "stay at home" [6] . But as social creatures, staying at home for a long time may cause many health problems [7] . Studies have shown [8] that if people stay at home for a long time, they may cause some psychosomatic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Another study performed in the USA showed that 48% of obese patients exercised less, 50% increased food stockpiling and about 60% increased stress-related eating, while 73% of them reported increased anxiety and 84% augmented depression since the confinement was initiated ( 33 ). A recent USA survey indicated that about 90% of responders spent more time at home and 22% gained 5–10 pounds, mostly due to absence of dietary restraint, stress-stimulated eating, and reduced physical activity imposed by COVID-19 confinement ( 34 ). Furthermore, an Italian survey performed in April 2020 indicated that weight gain was observed in almost 50% of the population, despite some positive self-implemented life style modifications ( 35 ).…”
Section: Physical Activity and Covid-19mentioning
confidence: 99%